Clinic Case of Rare Type VI Osteogenesis Imperfecta - Olga N. Ignatovich; Leyla S. Namazova-Baranova; Tea V. Margieva; Natalia V. Zhurkova; Kirill V. Savostyanov; Alexander V. Pushkov (Педиатрическая фармакология)
Osteogenesis imperfect is genetically heterogeneous group of diseases which are characterized by bone brittleness and fractures. It was thought for a long time that this is happening due to mutations in collagen genes. However, within past decade the understanding of osteogenesis imperfecta etiology has changed as a result of genetics development. The majority of all cases is related to mutations in collagen genes whereas rare mostly recessive forms are related to mutations in genes encoding collagen post-translational modification. Mutations in SERPINF1 gene were chosen as molecular cause of osteogenesis imperfecta type VI in 2011. Thus the new pathophysiology of this disease was revealed. Children with osteogenesis imperfecta type VI have high-frequency of fractures despite the management with bisphosphonates because mineralized bone osteoid is considerably reduced.